2015
DOI: 10.1021/acs.inorgchem.5b02703
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining Oxidation States during the Synthesis of 2-Rhodaoxetanes from Olefins

Abstract: Herein, we report experimental, spectroscopic, and computational data that indicate that a rhodium ethylene complex, formally described as rhodium(I) and which forms a 2-rhoda(III) oxetane following reaction with H2O2, is more accurately described as a rhodium(III) metallacyclopropane. X-ray absorption spectroscopy clearly demonstrates a change in the oxidation state at rhodium following ligand coordination with tris(2-pyridylmethyl)amine. Both NMR and density functional theory studies suggest a high energy ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Based on literature precedent, the reduction of Rh III to Rh I is expected to shift the rising portion of the K-edge to lower energy by 2-3 eV. 19,20 Indeed, we observe a significant difference in both the position and shape of the K-edge between [Rh III Cp*(phen)Cl] + and Rh I Cp*(phen) ( Figure S20). The Rh K-edge for [Rh III Cp*(phen)Cl] + has an inflection point at 23,226.5 eV, while the Rh K-edge for Rh I Cp*(phen) onsets earlier and has two inflection points at 23,225.6 and 23,231.7 eV ( Figure S21).…”
Section: Electrochemistry and X-ray Absorption Spectroscopy Of Gcc-rhsupporting
confidence: 59%
“…Based on literature precedent, the reduction of Rh III to Rh I is expected to shift the rising portion of the K-edge to lower energy by 2-3 eV. 19,20 Indeed, we observe a significant difference in both the position and shape of the K-edge between [Rh III Cp*(phen)Cl] + and Rh I Cp*(phen) ( Figure S20). The Rh K-edge for [Rh III Cp*(phen)Cl] + has an inflection point at 23,226.5 eV, while the Rh K-edge for Rh I Cp*(phen) onsets earlier and has two inflection points at 23,225.6 and 23,231.7 eV ( Figure S21).…”
Section: Electrochemistry and X-ray Absorption Spectroscopy Of Gcc-rhsupporting
confidence: 59%
“…Experimentally,t he 31 P{ 1 H} NMR spectrum of 1 up to 110 8Cr eveals no dynamic processes, indicatingt hat the barrier to carbonyl rotation is greater than 70 kJ mol À1 .W eh ave previously reported similar high barriers to rotation with ar hodium-olefin system. [8] Indeed, the metallaepoxide electromer of related nickel complexes have recently been invoked by the groups of Doyle [42] and Ogoshi [37] based on reactivity studies, andi sa lso shown explicitly in Group 4c omplexes that display similars tructural parameters to the nickel species discussed here. [58][59][60][61][62][63] Ambiguity in the electronic structureo ft hese nickel p-complexesh inderse fforts towards the rational design of nickel-catalysed processes.…”
Section: Introductionmentioning
confidence: 79%
“…[87] Given that the electron density of these systems are well described from DFTcalculations, we approached this same issue by applying natural resonance theory (NRT) [109][110][111] to expose different contributions to the overall electronic description ( Table 5). [8] In all cases, the Ni II metallacycle contributesl ittle to the overall electronic structure. TheN i 0 p-adduct and Ni I intermediate resonance structures account for > 80 %o ft he electronic structure in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations